Respecifying social change: the obsolescence of practices and the transience of technology - Mlynář, Jakub; Arminen, Ilkka (Frontiers in Sociology, 2023)
This article proposes that social change, a fundamental topic in sociological theory, can be productively revisited by attending to studies in ethnomethodology and conversation analysis (EM/CA). We argue that the corpus of EM/CA research, from the 1960s until the present day, provides details of the constitutive and identifying aspects of practices and activities that gradually transform into descriptions of obsolescent practices and activities, and that this corpus can be revisited to learn about the ways people used to do things. Taking landline and mobile telephony as a case in point, we show that the subtle details of conversational practices are anchored in the technology used as part of the contemporary lifeworld, and that they stand for the particularities of routine social structures of their time period. We also discuss the temporal aspects of the competences required on the part of members and analysts to make sense of encountered practices in terms of their ordinary recognizability and interactional consequentiality, pointing to the anchoring of social life in its historical time. Finally, we conclude by considering different ways of respecifying social change by attending to various kinds of historicity and obsolescence of social praxis.1 WWR stands for Walking with Romans, a digital "guide app … developed to facilitate physical and historical access to a little-visited site" (Smith et al., 2020, p. 226).2 EM and CA are approaches that have developed in sociology of the 1950s and 1960s, mainly in the work of Harold